If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (8x + 3) + (-9x + 9) = 0 Reorder the terms: (3 + 8x) + (-9x + 9) = 0 Remove parenthesis around (3 + 8x) 3 + 8x + (-9x + 9) = 0 Reorder the terms: 3 + 8x + (9 + -9x) = 0 Remove parenthesis around (9 + -9x) 3 + 8x + 9 + -9x = 0 Reorder the terms: 3 + 9 + 8x + -9x = 0 Combine like terms: 3 + 9 = 12 12 + 8x + -9x = 0 Combine like terms: 8x + -9x = -1x 12 + -1x = 0 Solving 12 + -1x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + -1x = 0 + -12 Combine like terms: 12 + -12 = 0 0 + -1x = 0 + -12 -1x = 0 + -12 Combine like terms: 0 + -12 = -12 -1x = -12 Divide each side by '-1'. x = 12 Simplifying x = 12
| 21n+3=7n-3 | | 3-6n=12+3 | | ln(x)=0.0875 | | log(x)=0.085 | | 14x-3x=1.5x+5 | | .7*x=402 | | 4j(5j)= | | (20,0+9,0)+(20,0+6,0)= | | x*x*x-2x*2x-15x=0 | | 5x+10=-12x-1 | | 28x^3-84x=0 | | 0=x^3-6x^2+16 | | 5n+12=an-16 | | y-3=67-4 | | 2x-7=8(x-3) | | log8N=2/3 | | 2x-7=8x(x-3) | | 5x^2+24y=-6y+126 | | t+-3=13 | | 17-4x=-8x+17 | | cos(pi/6) | | 11-6.5=20-x | | x(x)+6x+1=0 | | t+8+6=15 | | 3x=9/x^2 | | 4x(4x)-x+5=0 | | (7x+10)+(9x-2)= | | 5-s=3 | | (6x+2)-40=90 | | 6x+2-40=90 | | t-5+6=15 | | 5xy^2=y |